ANALISIS PENGARUH INKLUSI EKONOMI DIGITAL TERHADAP PERTUMBUHAN EKONOMI DAN DISTRIBUSI PENDAPATAN DI INDONESIA - Ku, Feky; Kaluge, David Kaluge (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
With the use of technology increasing so rapidly as time goes by, the government must facilitate the use of technology and also invest more in technology so that the effects of using this technology can be felt by all levels of society. This study aims to analyze how there is an effect of the use of digital technology on economic growth and income distribution. The variables used in this study are economic growth and income distribution as the dependent variable, while digital technology is the independent variable. The research model used is the convergence model, which has a significant level of less than 0.05. The result of this study is that all digital technology variables have a significant effect on economic growth and income distribution.